MULTI-CRITERIA DECISION MAKING FOR PERFORMANCE APPRAISAL OF HEALTHCARE PROFESSIONALS: A LITERATURE REVIEW - Rifan Eka Putra Nasution; April Yanti Pohan; Bakti Hadomuan; Julham Sihombing; Nurintan Asyiah Siregar (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This literature review synthesizes contemporary evidence on the application of Multi-Criteria Decision Making (MCDM) methodologies in the performance appraisal of healthcare professionals. Traditional appraisal systems are often critiqued for their limited ability to address the multifaceted nature of healthcare practice, which encompasses clinical competence, patient safety, ethical conduct, communication, and organizational contribution. A comprehensive analysis of seven studies published between 2019 and 2025 reveals that MCDM approaches, particularly AHP, TOPSIS, VIKOR, PROMETHEE, and fuzzy-based models, have been widely employed to structure complex appraisal processes involving multiple and sometimes conflicting criteria. These methods enhance transparency, consistency, and objectivity in appraisal systems, while facilitating the integration of expert judgment and stakeholder participation. Despite these advantages, significant implementation challenges persist, including the difficulty in defining relevant performance criteria, selecting appropriate MCDM methods, and achieving consensus among evaluators. While MCDM is well established in clinical decision-making and healthcare procurement, its direct application to healthcare professional appraisal remains underexplored. Evidence suggests that well-designed MCDM-based systems can improve decision quality and support organizational improvement in healthcare settings. However, empirical data on their impact on professional satisfaction and workforce development are limited, indicating a need for further research. This review underscores the potential of MCDM as a foundational framework for modernizing performance appraisal in healthcare, and identifies critical gaps for future scholarly inquiry